Spatial chloroplast-to-nucleus signalling involving plastid–nuclear complexes and stromules. (22nd June 2020) - Mullineaux, Philip M.; Exposito-Rodriguez, Marino; Laissue, Pierre Philippe; Smirnoff, Nicholas; Park, Eunsook
Abstract : Communication between chloroplasts and the nucleus in response to various environmental cues may be mediated by various small molecules. Signalling specificity could be enhanced if the physical contact between these organelles facilitates direct transfer and prevents interference from other subcellular sources of the same molecules. Plant cells have plastid–nuclear complexes, which provide close physical contact between these organelles. Plastid-nuclear complexes have been proposed to facilitate transfer of photosynthesis-derived H2 O2 to the nucleus in high light. Stromules (stroma filled tubular plastid extensions) may provide an additional conduit for transfer of a wider range of signalling molecules, including proteins. However, plastid–nuclear complexes and stromules have been hitherto treated as distinct phenomena. We suggest that plastid–nuclear complexes and stromules work in a coordinated manner so that, according to environmental conditions or developmental state, the two modes of connection contribute to varying extents. We hypothesize that this association is dynamic and that there may be a link between plastid–nuclear complexes and the development of stromules. Furthermore, the changes in contact could alter signalling specificity by allowing an extended or different range of signalling molecules to be delivered to the nucleus. This article is part of the theme issue 'Retrograde signalling from endosymbiotic organelles'.